THE ELASTIC INTERACTION OF LOCAL DEFECTS AT QUASIBRITTLE FRACTURE OF POLYMERS AND COMPOSITES BASED ON THEM - A. A. Valishin; T. S. Mironova (Тонкие химические технологии)
The article describes the mechanism of the elastic interaction of local micro-defects called holes, which are formed and accumulate in the forced elasticity area in front of the fracture crack in polymers. Amorphous glassy polymers such as PMMA are considered. The elastic field of the holes, their own elastic energy, the interaction energy of the holes and the strength of their two-body interaction are calculated. The interaction of holes leads to the fact that each hole is surrounded by an "atmosphere" of smaller holes. It is shown that the fracture crack is the source of its own elastic field. It is shown that the holes diffuse toward the front of the crack. The diffusive flux of the holes was calculated.